Respiratory Health and Indoor Air Pollution at High Elevation - Rosati, Jacky Ann (Arch Environ Occup Health, 2005)
In this research, the authors sought to provide experimental data on indoor air quality, and the resulting respiratory impact, for a high-elevation (4550 m), rural community in Ladakh, India. This community is of interest because the primarily nomadic residents burn biomass inside the home for heating and cooking. The concentrations of particulate matter (PM), endotoxin, and carbon monoxide were determined for 6 homes. Lung function data and induced sputum samples were collected for 9 female test-home subjects. In addition, lung function data were collected for 84 additional Ladakhi highlanders at this location. Sputum from 3 visiting scientists (sojourners) was collected and analyzed as well. The average PM concentration ranged from 2 mg/m(3) to 7 mg/m(3), with 85% of the sampled PM sized as respirable. The average endotoxin concentration ranged from 2.4 ng/m(3) to 19 ng/m(3), and average carbon monoxide levels ranged from 50 ppm to 120 ppm. Lung function values for the highlander population and the test-home subjects were equal to or greater than predicted, despite the highlanders’ significant exposure to indoor pollutants. An induced sputum analysis revealed a significantly greater total inflammatory cell count (M ± SD, 10(5) cell/mg) in the Ladakhi natives than in the sojourners (107.5 ± 75.2 vs 7.1 ± 8.1, p .01). Although the high levels of indoor pollutants did not correlate with significant decrements in lung function, the induced sputum analysis revealed marked airway inflammation dominated by macrophages and neutrophils. It appears that augmented lung mechanics of this high-altitude population are adaptive to reduce the work of breathing; thus, decrements in lung function go undetected because the true predicted values are greater than expected.